Long‐Term Efficacy of a Double‐Blind, Placebo‐Controlled, Randomized Study for Repetitive Sphenopalatine Blockade With Bupivacaine vs Saline With the Tx360® Device for Treatment of Chronic Migraine. Issue 4 (31st March 2015) - Cady, Roger K.; Saper, Joel; Dexter, Kent; Cady, Ryan J.; Manley, Heather R.
<x xml:space="preserve">Abstract</x> Background This study aims to determine if repetitive sphenopalatine ganglion (SPG) blockades with 0.5% bupivacaine delivered with the Tx360® device results in long‐term improvement in chronic migraine (CM). The SPG is a small concentrated structure of neuronal tissue that resides within the pterygopalatine fossa in close proximity to the sphenopalatine foramen and is innervated by the maxillary division of the trigeminal nerve. In a previous article, these authors reported repetitive SPG blockades with 0.5% bupivacaine delivered by the Tx360® device, which was an effective and well‐tolerated intervention to incrementally decrease baseline headache intensity of subjects with CM. Methods This was a double‐blind, parallel‐arm, placebo‐controlled, randomized pilot study using a novel intervention for acute treatment in CM. A total of 41 subjects were enrolled at two headache specialty clinics in the USA. Eligible subjects were between 18 and 80 years of age and had a history of CM defined by International Classification of Headache Disorders‐II definition. Subjects were allowed a stable dose of migraine preventive medications that was maintained throughout the study. Following a 28‐day baseline period, subjects were randomized by computer‐generated lists 2:1 to receive 0.3 cc of 0.5% bupivacaine or saline, respectively, delivered with the Tx360® twice a week for 6 weeks. Secondary end‐points reported in this manuscript include post‐treatment measures including number of headache days and quality of life measures. Results The final data set included 38 subjects: 26 in the bupivacaine group and 12 in the saline group. Our primary end‐point for the study, difference in numeric pain rating scale scores, was met and reported in a previous article. The supplemental secondary end‐points reported in this manuscript did not reach statistical significance. When looking collectively at these end‐points, trends were noticed and worthy of reporting. Subjects receiving bupivacaine reported a decrease in the number of headache days 1 month post‐treatment (Mdiff = −5.71), whereas those receiving saline only saw a slight improvement (Mdiff = −1.93). Headache Impact Test 6 scores were decreased in the bupivacaine group at 1 month (Mdiff = −5.13) and 6 months (Mdiff = −4.78) post‐treatment, but only a modest reduction was seen for those receiving saline at 1 and 6 months, respectively (Mdiff = −2.08, Mdiff = −1.58). Furthermore, subjects receiving bupivacaine reported a reduction in acute medication usage and improved quality of life measures (average pain in the previous 24 hours, mood, normal work, and general activity) up to 6 months post‐treatment. The changes in these measures for the saline group were minimal. Conclusions Data from this exploratory pilot study suggest that there may be long‐term clinical benefits with the use of repetitive SPG blockades with bupivacaine delivered with the simple to use Tx360® device. These include a sustained reduction of headache days and improvement in several important quality of life assessments. The SPG blockades were not associated with any significant or lasting adverse events. Further research on SPG blockade is warranted.